Stroke Risk and Mortality in Patients With Ventricular Assist Devices. Issue 11 (November 2016) - Parikh, Neal S.; Cool, Joséphine; Karas, Maria G.; Boehme, Amelia K.; Kamel, Hooman
Abstract : Background and Purpose—: Ventricular assist devices (VADs) have advanced the management of end-stage heart failure. However, these devices are associated with hemorrhagic and thrombotic complications, including stroke. We assessed the incidence, risk factors, and outcomes of ischemic and hemorrhagic stroke after VAD placement. Methods—: Using administrative claims data from acute care hospitals in California, Florida, and New York from 2005 to 2013, we identified patients who underwent VAD placement, defined by the International Classification of Diseases, Ninth Revision, Clinical Modification code 37.66. Ischemic and hemorrhagic strokes were identified by previously validated coding algorithms. We used survival statistics to determine the incidence rates and Cox proportional hazard analyses to examine the associations. Results—: Among 1813 patients, we identified 201 ischemic strokes and 116 hemorrhagic strokes during 3.4 (±2.0) years of follow-up after implantation of a VAD. The incidence of stroke was 8.7% per year (95% confidence interval [CI], 7.7–9.7). The annual incidence of ischemic stroke (5.5%; 95% CI, 4.8–6.4) was nearly double that of hemorrhagic stroke (3.1%; 95% CI, 2.6–3.8). Women faced a higher hazard of stroke than men (hazard ratio, 1.6; 95% CI, 1.2–2.1), particularly hemorrhagic stroke (hazard ratio, 2.2; 95% CI, 1.4–3.4). Stroke was strongly associated with subsequent in-hospital mortality (hazard ratio, 6.1; 95% CI, 4.6–7.9). Conclusions—: The incidence of stroke after VAD implantation was 8.7% per year, and incident stroke was strongly associated with subsequent in-hospital mortality. Notably, ischemic stroke occurred at nearly twice the rate of hemorrhagic stroke. Women seemed to face a higher risk for hemorrhagic stroke than men.